Factors affecting mechanisation in the South African platinum mining industry. - Manilall, Nishall (My University, 2016)
Although mine mechanisation is not a new concept to the mining industry, the majority of platinum mines in South Africa are still using conventional methods to mine. Given the current South African economic climate, these conventional methods are not sustainable for the platinum industry. South African mining enterprises are faced with numerous challenges, some of which are: low labour productivity, increasing operational costs, and challenges associated with greater mining depths. These challenges are forcing platinum producers to rethink how they mine. In order for platinum producers to remain relevant and competitive, mechanisation of mines is a viable option that mining stakeholders must embrace. Given this context, this research aims to provide insight into the factors that affect mine mechanisation in the South African platinum mining industry. A quantitative research methodology was adopted, whereby 142 online questionnaires were sent out to gather information from different mining stakeholders. The mining stakeholders comprised four groups, namely: mining house technical staff, mining house management staff, consultants, and mining equipment vendors. The data that was gathered was subsequently subjected to the following statistical analyses: descriptive statistics, exploratory factor analysis (EFA), and analysis of variance (ANOVA). The findings of the research highlighted favourable and unfavourable factors that affect mine mechanisation in the South African platinum mining industry. Some of the factors, including mine safety and productivity, are perceived as very favourable, while skills shortages and job losses are viewed as unfavourable for mechanisation. The exploratory factor analysis was instrumental in determining the underlying structure of the data and revealed that a four factor structure exists. These factors are: deciding elements of mechanisation, implementation of mechanisation, benefits of mechanisation, and impact of people on mechanisation. Finally, an ANOVA was conducted to identify differences in stakeholder views, and revealed ii that no significant differences in perceptions exist between the different stakeholder groups. It is envisaged that this study will assist mining stakeholders to better grasp the factors that influence mechanisation, and enable them to effectively strategize when undertaking mechanisation projects. Further, the findings of this research contributes to the limited body of knowledge in the platinum mining sphere and provides a platform for further research on mine mechanisation. Search words: mechanisation, mining, platinum, exploratory factor analysis, analysis of variance.
MBA
Keywords: Platinum mines and mining.Platinum group industry -- South Africa. Mineral industries -- Automation.